Understanding acceptability of digital health technologies among francophone-speaking communities across the world: a meta-ethnographic study - Gauthier-Beaupré, Amelie; Grosjean, Sylvie (Frontiers in Communication, 2023)
Introduction: Increasingly, people are turning toward digital health technologies to support their care management, communication with health professionals, and performing activities of daily living. Digital health technologies may be well implemented in clinical practices in several jurisdictions, but the influence of sociocultural factors may sometimes be neglected. To increase use and sustainability of these innovative solutions in health care, we need to understand acceptability among diverse groups of the population such as linguistically diverse populations. Francophone-speaking populations in Canada, for example, are known to endure challenges with income, health and difficulties associated with living in rural areas which impede on their likelihood to use digital health technologies. As part of the University of Ottawa International Francophonie Research Chair on Digital Health Technologies, this study aimed to understand the conditions that make digital health technologies acceptable among francophone-speaking communities. Methods: Using a meta-ethnography methodology, this study synthesizes international qualitative research on social acceptability of digital health technology among francophone-speaking communities. We focused on four types of digital health technologies: telemedicine, mobile technologies, wearable technologies, and robotic technologies. Using Noblit and Hare's 7 phase approach to conducting a meta-ethnography, we were able to get a comprehensive synthesis and understanding of the research landscape on the issue. Studies published between 2010 and 2020 were included and synthesized using NVivo, excel and a mind mapping technique. Results: Our coding revealed that factors of social acceptability for digital health technologies could be grouped into the following categories: care organization, self-care support, communication with care team, relational and technical risks, organizational factors, social and ethical values. Our paper discusses the themes evoked in each category and their relevance for the included digital health technologies. Discussion: In discussing the results, we present commonalities and differences in the social acceptability factors of the different digital health technologies. In addition, we demonstrate the importance of considering sociocultural diversity in the study of social acceptability for digital health technologies. Implications: The results of this study have implications for practitioners who are the instigators of digital health technology implementation with healthcare service users. By understanding factors of social acceptability among francophone-speaking communities, practitioners will be better suited to propose and support the implementation of technologies in ways that are suitable for these individuals. For policymakers, this knowledge could be used for developing policy actions based on consideration for diversity.

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Le programme de télésanté de prévention des chutes Marche vers le Futur : développement et retombées d’une communauté de pratique franco-canadienne - O’Neil, Jennifer; Dionne, Nathalie; Cardinal, Dominique; Savard, Jacinthe (Minorités linguistiques et société, 2025)
Résumé Le programme de télésanté Marche Vers le Futur (MVF) a eu un impact positif sur le bien-être des personnes âgées francophones et sur leur accès aux services de prévention des chutes au Canada. L’objectif de ce projet était de développer et de mettre en place une communauté de pratique (CdP) facilitant le partenariat et le partage des connaissances entre les animateurs du programme MVF. La création de cette CdP a permis à vingt-deux animateurs de cinq provinces de partager des stratégies de recrutement, de promotion du programme et de sensibilisation quant aux besoins des personnes âgées francophones au pays. Quatre rencontres virtuelles ont permis d’identifier les obstacles à la pérennité de MFV, les facteurs facilitant la mobilisation des connaissances ainsi que les initiatives de formation continue. La CdP a permis de renforcer les réseaux de partenariat entre les chercheurs et les animateurs du programme MVF, ce qui pourrait avoir un impact important sur l’équité en santé chez les personnes âgées francophones vivant en situation minoritaire au Canada. Abstract Marche vers le Futur (MVF) is a telehealth program that has demonstrated a positive impact on the access to fall prevention services in Canada and the wellness of older Francophone adults living in minority situations. This project aimed to develop and implement a community of practice (CoP) to facilitate partnership and knowledge-sharing between MVF program facilitators across francophone communities in Canada. The creation of this CoP enabled twenty-two facilitators from five provinces to share strategies for recruiting, promoting, and sustaining the program as well as continuing to raise awareness around the importance of health prevention services tailored for older Francophone adults in Canada. Four virtual meetings were held to identify sustainability barriers, knowledge mobilisation facilitators, and continuing education initiatives. The CoP allowed to strengthen the partnership between researchers and program facilitators across diverse provinces which could impact health equity among older Francophone adults living in minority communities in Canada.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.